Assessing healthcare digitalisation in Ghana: A critical realist’s approach - Preko, M.; Boateng, R. (Health Policy and Technology, 2020)
Background: The emergence of digital technologies within the health sector has presented opportunities for improving medical care while strengthening health systems across the globe. Despite this promise, the extent of digitalisation, especially in developing countries, somewhat remains undetermined. Such knowledge is needed to learn and shape future advances in the sector. The purpose of this study, there- fore, is to explore the generative mechanisms of digitalisation in the Ghanaian health sector, in order to understand and assess the extent of digitalisation, based on the digitalisation outcomes of the respective generative mechanisms. Methods: Underpinned by the critical realism philosophy, a single case study approach was adopted to explore the generative mechanisms of digitalisation in the Ghanaian health sector, and how the varying degrees of digitalisation are interpreted and explained in the empirical world. Results: The study found five generative mechanisms of digitalisation in the Ghanaian health sector. These were Standardisation, Convergence and Connectivity, Storage Systems, Financial Transparency, and Data Security. Full activation of these mechanisms revealed that the first three generative mechanisms achieved high levels of digitalisation based on the extent of organisational transformations observed af- ter the digitalisation process, as compared to the last two generative mechanisms which were rated as average. Discussion: This study concludes that the extent of digitalisation in Ghana’s health sector is more of reality than mere perception. The demonstration of how critical realism can be used to unearth insights into the extent of healthcare digitalisation in a developing country context spells the contribution of this paper.
Research Article
Keywords: Healthcare; Critical Realism; Digitalisation; Electronic Medical Record; Developing Country